The effect of terminal substituents on crystal structure, mesophase behaviour and optical property of azo-ester linked materials. Issue 12 (25th September 2016) - Karim, Md. Rabiul; Sheikh, Md. Rezaul Karim; Yahya, Rosiyah; Mohamad Salleh, Noordini; Lo, Kong Mun; Mahmud, H.N.M Ekramul
ABSTRACT: A series of azo-ester linked mesogen containing liquid crystalline acrylate compoundsC1-C6 having different terminal groups (–F, –Cl, –Br, –OCH3, –OC2 H5 and –OC3 H7 ) were successfully synthesised and characterised. The chemical structure, purity, thermal stability, mesophase behaviour and optical property of the synthesised compounds were investigated by different instrumental techniques. X-ray crystal structure showed that compoundsC1, C4 andC5 exhibited more stable E configuration with two bulky group in the opposite side of the N=N double bond motifs. The fluoro-substituted derivative (C1 ) is connected by the R 1 2 (5) type of C–H…O hydrogen bond motifs whereas the molecules ofC4, andC5 are connected to each other by means cyclic R 2 2 (8) type of C–H…O hydrogen bond motifs. Thermogravimetric study revealed that the investigated compounds exhibited excellent thermal stability. All the compounds showed enantiotropic liquid crystal (LC) phase behaviour and the mesophase formation was greatly influenced by the terminal substituents. Alkoxy (–OCH3, –OC2 H5 and –OC3 H7 ) substituted compounds exhibited greater mesophase stability than those of halogen (–F, –Cl and –Br) terminated derivatives. UV-vis spectroscopic study revealed that the investigated compounds exhibited a broad absorption band around 300–420 nm with absorption maximum ( λ max ) of nearly 370 nm. GRAPHICAL ABSTRACT: